The Nizari Ismailis and the End of Their Presence in Iran 654487 (H 12561094 / AD) (Journal of the College of Basic Education, 2023)
Throughout its long history, the Islamic world witnessed many religious movements.Most of them revolve around a basic point, which is the caliphate, the mandate of the Covenant, and who is more deserving of assuming it.Nazareth Ismailism is one of these movements that emerged relatively late in the history of Islam.The Arab Islamic State left an unforgettable mark, especially in Iran, which was one of theThe most important quarters of Khorasan, as this group found there the climate and conditions suitable for its spreadIt lasted for more than a century and a half.In this research, we will learn about the most important names that have been given to this group since its emergence.In Fatimid Egypt and its end in Iran.The emergence of this sect during the era of its founder, Al-Hassan bin Al-Sabah, and his adoption of the Citadel of Death as a main center.He has to send his preachers and followers from there to the rest of Iran and the Islamic world to spread his call.and carrying out his orders, and his call met with great success due to the circumstances that prevailed in the Islamic world.then.We will also briefly discuss the efforts of the Seljuk sultans in Persia and the Ayyubids in Syria to eliminateagainst them, and highlighted their activities against their opponents.We will also explain the conditions of the Nizari Ismailis prior to the Mongol invasion and the changes that took place inOn their policy towards the Abbasid caliphate, and then their attitude towards Sultan Jalal al-Din Munkabarti.We will review in some detail the Mongol invasion of their castles in Iran and its causes.And their conditions during this period and the policy that Hulagu Khan followed to storm these castles, whichIt was crowned with success, and the leader of the Nazarite Ismailis was killed and they disappeared from the scene of events in Iran.Finally, it should be noted that we did not find Nizari Ismaili sources that wrote downthe historical events that they experienced and that had the greatest impact on highlighting their point of view towardsthese events.